Biological differences and unilateral cross-protection between biotypes of Cowpea aphid-borne mosaic virus - Maia, Laianny; Lima, José Albersio; Nascimento, Aline Kelly; Rabelo Filho, Francisco de Assis (Revista Ciência Agronômica, 2016)
Passion fruit (Passiflora edulis) and cowpea (Vigna unguiculata) are two agricultural crops of considerable economic importance in Northeastern Brazil. Fruit woodiness caused by isolates of Cowpea aphid-borne mosaic virus biotype P (CABMV-P) is the most important virus disease that occurs on passion fruit in Brazil and the biotype cowpea (CABMV-C) is responsible for the most common and important virus disease of cowpea in Northeastern Brazil. The objective of the present research was to determine the biological relationships between isolates of biotype CABMV-C obtained from cowpea (CABMV-CFor and CABMV-CBv) and isolates of biotype CABMV-P obtained from passion fruit (CABMV-PMild and CABMV-PSevere) in common hosts. In host range studies involving 25 plant species only Canavalia ensiformis and Macroptilium lathyroides were shown to be common systemic hosts for all virus isolates. Cross protection studies were developed between CABMV-PMild and CABMV-PSevere in passion fruit and between CABMV-PSevere and CABMV-CFor in C. ensiformis. Unilateral cross protection was detected between CABMV-PSevere and CABMV-CFor in C. ensiformis, but CABMV-PMild did not cross protect passion fruit against CABMV-PSevere.